You should try to retake the picture can’t c anything
Answer:
I think the answer is x is 16 and y is 20? I could be wrong tho
Step-by-step explanation:
First, subtract -7 from -1 to get 8.
Then, add the 12 and you get 16 for x.
First, subtract 7y from 9x to get 2y
Then, add 4 to get 20 for y.
Answer:
Total people = 240
Step-by-step explanation:
Let the total number of people by 'x'.
![\sf \text{Number of men =$ \dfrac{1}{4}*x$} \\](https://tex.z-dn.net/?f=%5Csf%20%5Ctext%7BNumber%20of%20men%20%3D%24%20%5Cdfrac%7B1%7D%7B4%7D%2Ax%24%7D%20%5C%5C)
![\sf \text{Number of women =$\dfrac{1}{3}x$}](https://tex.z-dn.net/?f=%5Csf%20%5Ctext%7BNumber%20of%20women%20%3D%24%5Cdfrac%7B1%7D%7B3%7Dx%24%7D)
Number of children = 100
When we subtract the total number of men and women from the total people 'x', we get the number of children.
![\sf x - \left(\dfrac{1}{4}x+\dfrac{1}{3}x\right)= 100\\\\x - \left(\dfrac{1*3}{4*3}x+\dfrac{1*4}{3*4}x\right)=100\\\\](https://tex.z-dn.net/?f=%5Csf%20x%20-%20%5Cleft%28%5Cdfrac%7B1%7D%7B4%7Dx%2B%5Cdfrac%7B1%7D%7B3%7Dx%5Cright%29%3D%20100%5C%5C%5C%5Cx%20-%20%5Cleft%28%5Cdfrac%7B1%2A3%7D%7B4%2A3%7Dx%2B%5Cdfrac%7B1%2A4%7D%7B3%2A4%7Dx%5Cright%29%3D100%5C%5C%5C%5C)
![x- \dfrac{4+3}{12}x=100\\\\x - \dfrac{7}{12}x = 100\\\\ \dfrac{12}{12}x-\dfrac{7}{12}x = 100\\\\ \dfrac{5}{12}x=100\\](https://tex.z-dn.net/?f=x-%20%5Cdfrac%7B4%2B3%7D%7B12%7Dx%3D100%5C%5C%5C%5Cx%20-%20%5Cdfrac%7B7%7D%7B12%7Dx%20%20%20%3D%20100%5C%5C%5C%5C%20%5Cdfrac%7B12%7D%7B12%7Dx-%5Cdfrac%7B7%7D%7B12%7Dx%20%3D%20100%5C%5C%5C%5C%20%20%20%20%20%20%20%20%20%20%5Cdfrac%7B5%7D%7B12%7Dx%3D100%5C%5C)
![\sf x = 100*\dfrac{12}{5}\\](https://tex.z-dn.net/?f=%5Csf%20x%20%3D%20100%2A%5Cdfrac%7B12%7D%7B5%7D%5C%5C)
x = 20 * 12
x = 240
<h3> Total number of people = 240</h3>
Answer:
the factors of x^3-1 are ![x^3 -1 = (x-1) (x^2 +x+1)\\](https://tex.z-dn.net/?f=x%5E3%20-1%20%3D%20%28x-1%29%20%28x%5E2%20%2Bx%2B1%29%5C%5C)
Step-by-step explanation:
We need to find factors of x^3 -1
![x^3-1 \\(x)^3 -(1)^3\\We \,\, know\,\, a^3 -b^3 = (a-b) (a^2 +ab + y^2) \\So, \,\, using\,\, the \,\, formula\,\,\\Here\,\, a= x \,\,and\,\, b= 1\\(x)^3 -(1)^3 = (x-1) (x^2 +x+1)\\](https://tex.z-dn.net/?f=x%5E3-1%20%5C%5C%28x%29%5E3%20-%281%29%5E3%5C%5CWe%20%5C%2C%5C%2C%20know%5C%2C%5C%2C%20a%5E3%20-b%5E3%20%3D%20%28a-b%29%20%28a%5E2%20%2Bab%20%2B%20y%5E2%29%20%5C%5CSo%2C%20%5C%2C%5C%2C%20using%5C%2C%5C%2C%20the%20%5C%2C%5C%2C%20formula%5C%2C%5C%2C%5C%5CHere%5C%2C%5C%2C%20a%3D%20x%20%5C%2C%5C%2Cand%5C%2C%5C%2C%20b%3D%201%5C%5C%28x%29%5E3%20-%281%29%5E3%20%3D%20%28x-1%29%20%28x%5E2%20%2Bx%2B1%29%5C%5C)
So, the factors of x^3-1 are ![x^3 -1 = (x-1) (x^2 +x+1)\\](https://tex.z-dn.net/?f=x%5E3%20-1%20%3D%20%28x-1%29%20%28x%5E2%20%2Bx%2B1%29%5C%5C)